Analisis Perbandingan Kinerja Protokol Routing Multi-Copy Dan Single-Copy Berdasarkan Mobilitas Node Pada Delay Tolerant Network - Faris Naufal Al Farros; Rakhmadhany Primananda; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Delay Tolerant Network (DTN) is the solution of the stiffness of transferring information through the weak of internet network. The previous research of DTN mostly focuses on the way the protocol performance of Multi-copy and Single-copy utilizing one way and one mobility. So that's why the deepest research is needed to know the protocol performance of Multi-copy, Single-copy and 3 mobilities node. The test using 3 types of message size and 3 types of nodes with The One Simulator. The result of the research showing the highest value of Delivery probability with the message size is 10 MB with the percentage about 0,1842%, routing ProPHet mobility Shortes Path Map Based Movement with the number of node 50 with the percentage 0,0375%. The highest value of Average latency based on the message size and the number of node is routing epdemic (multicopy) with the node mobility Map Based Movement message size 45MB with the value 737,4527s. then the highest value of Overhead ratio based on the message size is routing First Contact mobility node Map Based Movement with the message size 45MB with the percentage 22,04%, routing ProPHet mobility node Map Based Movement the number of node is 10 with the value 25,0909%.